Understanding the Role of Mental Health Clubhouses in Promoting Wellness and Health Equity Using Pilinahā—An Indigenous Framework for Health. Issue 3 (21st September 2020) - Agner, Joy; Barile, John P.; Botero, Adriana; Cha, Tiffany; Herrera, Nikolas; Kakau, Tyra M.; Nakamura, Lisa; Inada, Megan; ,
Abstract: Individuals with severe mental illness need to be engaged in defining their own vision of wellness to promote equity and reduce disparities. This photovoice study helps define what wellness is and how it is achieved in mental health Clubhouses in Hawai'i. Results from a photovoice study with 43 members and staff were analyzed using Pilinahā, a Native Hawaiian framework for health. Pilinahā envisions health through connection to place, community, past and future, and one's better self. Within Clubhouses, connection to place included connection to 'āina (land) and the access to a safe space. Connection to community occurred through reciprocal social support, which developed kuleana (responsibility), and a sense of 'ohana (family) for many members who were previously isolated. Connection to one's better self‐involved positive identity change, development of hope, and pursuing opportunities within and outside the Clubhouse. Connection to past and future was described through individual narratives, remembering members who had died, and connection to cultural traditions. Overall, wellness was conceptualized as the ability to work toward dreams, engage in cultural practice, and feel accepted, respected, and valued—to be treated with aloha . Findings provide a culturally responsive perspective on wellness and illustrate the value of Clubhouses as a space for mental health recovery and transformative change. Highlights: Clubhouse members and staff in Hawai'i participated in a multi‐site photovoice process. This article describes what members found essential to wellness and how it can be achieved. Clubhouses provide a space for mental health recovery and transformative change.